Monitoring and Analyzing of Circadian and Ultradian Locomotor Activity Based on Raspberry-Pi - Vittorio Pasquali; Riccardo Gualtieri; Giuseppe D’Alessandro; Maria Granberg; David Hazlerigg; Marco Cagnetti; Fabio Leccese (Electronics, 2016)
A new device based on the Raspberry-Pi to monitor the locomotion of Arctic marine invertebrates and to analyze chronobiologic data has been made, tested and deployed. The device uses infrared sensors to monitor and record the locomotor activity of the animals, which is later analyzed. The software package consists of two separate scripts: the first designed to manage the acquisition and the evolution of the experiment, the second designed to generate actograms and perform various analyses to detect periodicity in the data (e.g., Fourier power spectra, chi-squared periodograms, and Lomb–Scargle periodograms). The data acquisition hardware and the software has been previously tested during an Arctic mission with an arctic marine invertebrate.